Identifying Higher Order Thinking Activation in English Textbook Mandated in Indonesian Senior High School - Misdi, Misdi; Syukur, Anton Muzaeni (Lingual Journal of Language and Culture, 2021)
This paper aims at investigating factual phenomenon of higher order thinking as it reflected in the reading activities of “ Bahasa Inggris SMA/MA XI ”. Using theory of Bloom’s taxonomy, this study used the content analysis method to identify reading features specifically for their essay questions and exercises and tasks of the English textbook. The data of essay reading questions were collected by using coding checklist . Three categories of higher order thinking ( analyze , evaluate , and create ) are discovered while the distribution of the higher order thinking level is higher than the lower order thinking level. The findings reveals higher order thinking activation and activities in the reading exercises and tasks  is unequal. It do, especially the create skills which pursued lower distribution es not provide treatment properly of the higher order thinking than the analyze skill and the evaluate skill Rather, this makes emphasis on the evaluate skills.